THE RITUAL OF MARRIAGE - Manan, Abdul (SCAD Independent, 2014)
This article explores the mating rituals in Labuhan Haji West - South Aceh. The goal is to express the values and profound ideas expressed by Aneuk Jamee society before and after the wedding ceremony itself. This research is a field of research and data collection through observation with utmost care and in-depth interviews of key informants. The research concludes that men are more active than women. Therefore man is personified as